Socialization and Providing Motivation on Health Professionals at National and International Levels: Challenges and Strategies for Students of State Vocational High School 3 Medan - Ritonga, Ahmad Hafizullah; ., Herlina; Harefa, Karnirius; Sitorus, Rotua Sumihar (JURNAL PENGMAS KESTRA (JPK), 2023)
Community service activities in the form of socializing and providing motivation regarding professional health workers at the national and international levels have been carried out at the Vocational High School (SMK) Negeri 3 Medan. This activity aims to provide participants with an understanding of the challenges of becoming professional health workers and strategies for becoming professional health workers at both the national and international levels, especially students of SMK Negeri 3 who have just graduated. This community service activity includes initial preparation, socialization related to health workers and the importance of becoming professional health workers, providing motivation related to challenges and strategies in becoming professional health workers both at national and international levels to activity participants, as well as distributing flyers related to information on private universities that affiliated with many health fields and successfully sending graduates abroad every year. This activity was attended by final-year students of SMK Negeri 3 Medan and teachers in the SMK Negeri 3 Medan environment. This activity has succeeded in providing information related to professional health workers and motivating them to become professional health workers at the national and international levels SMK students who are about to finish their education (graduate) and are interested in continuing to higher education, which is marked by the enthusiasm of the activity participants asked about tips on becoming professional health workers at the national and international levels.